A simple and convenient 3D printed temporal bone model for drilling simulating surgery. (2nd January 2022) - Yuan, Zhi-Ming; Zhang, Xiao-Dong; Wu, Shou-Wu; Nian, Zhong-Zhu; Liao, Jun; Lin, Wen; Zhuang, Li-Ming
Abstract: Background: It is still far away from most of us in that it requires complex 3D modeling. Aims/objectives: To investigate a more precision, simple, convenient and economical three-dimensional (3D) printed temporal bone model printed by a commercial desktop 3D printer, which can be widely promoted and applied in the training of beginners in otology. Material and Methods: The CT data of the temporal bone were imported into Mimics to construct a 3D digital model of the temporal bone. After loaded into a high-precision 3D printer, a high-precision temporal bone model was printed at a scale of 1:1. Then, the model was evaluated by 5 senior attending physicians, including its morphological accuracy, simulation about surgery, advantages and educational value, using the 7-point Likert scale. Results: A life-like temporal bone model was successfully printed out. Five senior attending physicians all thought that the printed model was similar to the natural temporal bone in physical properties and the haptic sensation of bone drilling, and was accurate, simple, convenient and effective. In addition, the model was considered to be of high application value in the teaching of temporal bone anatomy and surgery simulation, which had a material cost of only 3 dollars. Conclusions: The high-precision 3D printed temporal bone model is highly similar to the natural temporal bone, and can be conveniently and effectively used in the training of simulating temporal bone surgery for beginners in otology. Its production is simple and economical, so it can be popularized on a large scale.